Factors Influencing Rumination in Post-traumatic Growth: A Systematic Review and Meta-analysis - Mehrnesa Shahabi; Jafar Hasani; Majid Asadpour (Caspian Journal of Health Research)
Background: Traumatic events can have profound psychological impacts, ranging from distress to positive transformations known as post-traumatic growth (PTG). Rumination—repetitive thinking about the trauma—has been posited to influence PTG, though evidence on its effects remains mixed. Some studies suggest that deliberate and intrusive rumination may positively associate with PTG, while others find that intrusive rumination can negatively impact PTG. Objectives: This systematic review and meta-analysis aimed to explore the association between rumination and PTG after traumatic experiences, with a focus on the factors affecting deliberate and intrusive rumination in the development of PTG. Methods: A comprehensive search of seven databases—Scopus, PubMed, PsycINFO, Science Direct, Web of Sciences, ProQuest, and Google Scholar—was conducted for peer-reviewed studies from January 1, 1996, to February 10, 2024. Studies were included if they quantitatively measured both PTG and rumination and met sample size requirements. In total, 56 studies were included in the analysis, following PRISMA guidelines. Results: The meta-analysis revealed a significant positive association between rumination and PTG. Deliberate rumination was consistently linked with heightened PTG, suggesting that it may help individuals reframe their experiences positively. The association between intrusive rumination and PTG appeared more complex, potentially moderated by trauma severity, coping mechanisms, and social support. The findings also indicated that age was not a moderating factor, while gender significantly influenced the relationship, with mixed-gender studies reporting larger effect sizes. Conclusions: This review underscores that rumination, particularly deliberate rumination, plays a substantial role in fostering PTG. While intrusive rumination's impact on PTG may vary, engaging in rumination generally supports PTG in both short- and long-term contexts. Gender differences in this relationship warrant further exploration to tailor interventions that promote PTG effectively.